Synthesis and Crystal Structure of Tetra[pyridine]diperchlorato-K2 O-Cadmium(II) - Feng Ding, Cai; Zhu, Mei; Li, Xue-Mei; Sheng Zhang, Shu; Xu, Hong; Ouyang, Ping-Kai (Asian Journal of Chemistry, 2010)
The crystal structure of [Cd(C5H5N)4(ClO4)2] has been determined by single crystal X-ray diffraction method. The crystal belongs to orthorhombic system, space group P212121 with unit cell constants a = 10.368(2), b = 14.403(3), c = 16.647(3) Å, V = 2485.9(8) Å3, Z = 4, Dc = 1.677 g/cm3, μ = 1.145 mm-1, F(000) = 1256, R and wR are 0.0447 and 0.1304, respectively for 4867 unique reflections with 4450 observed reflections (I > 2σ(I). The central Cd(II) atom is coordinated by four N atoms from four pyridine ligands and two O atoms from two perchlorate counter-ions. The coordination geometry is slightly distorted octahedral, with the four N atoms occupying the equatorial positions, while two O atoms being in the axial positons. The packing is stabilized by C-H...O intermolecular interactions.